Startups: study opening and management process - Figueira, Kristina Kieling; Hörbe, Tatiane de Andrade Neves; Vargas, Katiuscia de Fátima Schiemer; Machado, Emanuelly Comoretto; de Moura, Gilnei Luiz (Revista de Administração da UFSM, 2017)
This study aims to understand the process and actions performed to open and manage startups. For this, an exploratory and qualitative research was carried out using semi-structured interviews as data collection technique, with seven partners/managers of startups from the city of Santa Maria, Rio Grande do Sul, based on the Reynolds model (2000). The results showed that startups managers take from four to six months to formulate the idea of the business and put it into practice, with investments considered by them to be relatively low. In addition, it was verified that the investigated startups, with all their innovative and differentiation potential in relation to the other businesses, besides searching for specific management methodologies and directed to their nature and formation, also use traditional management tools like the known and disseminated business plan. It was also noticed that startups come across with typical problems of customers acceptance, lack of financial resources, lack of management knowledge and excessive bureaucracy of public agencies when they start their activities and that their managers, although they have styles oriented to the innovation and practicality, as well as people-oriented management, take a reactive stance on identifying and solving problems.